Odpowiedzi

2009-11-17T20:25:43+01:00
1/3x - 1/2y = 2
1/4x + 1/3y = 1/12

-1/2y = 2- 1/3x
1/4x + 1/3y= 1/12

1/2y = -2 + 1/3x /:1/2
1/4x + 1/3y= 1/12

y= -4 + 2/3x
1/4x + 1/3(-4 + 2/3x) = 1/12

y= -4 + 2/3x
1/4x - 4/3 + 2/9x = 1/12

y= -4 + 2/3x
17/36x = 1/12 + 4/3

y= -4 + 2/3x
17/36x = 17/12 /:17/36

y= -4 + 2/3x
x =3

y= -4 + 2/3 *3
x =3

y= -2
x =3


2009-11-17T20:28:40+01:00
1/3x - 1/2y = 2 /*6
1/4x + 1/3y = 1/12 /* (-12)

2x - 3y = 12 /*3
-3x - 4y = -1 /*2

6x - 9y = 36
-6x - 8y = -2

-17y = 34 / /(-17)

y=-2

2x - 3y = 12

2x - 3 * (-2) = 12

2x + 6 = 12

2x = 12 -6

2x = 6

x = 3
y = -2
2009-11-17T20:38:49+01:00
1/3x - 1/2y = 2 /*6
1/4x + 1/3y = 1/12 /*12

2x-3y=12
3x+4y=1

2x=12+3y /:2
3x+4y=1

x=6+3/2y
3*(6+3/2y)+4y=1

18+9/2y+4y=1
x=6+3/2y

x=6+3/2y
9/2y+4y=-17 /*2

x=6+3/2y
9y+8y=-34

17y=-34 /:17
x=6+3/2y

y=-2
x=6-3

x=3
y=-2